Analisa Pengaruh Terhadap Kualitas Transfer Data pada Jaringan Computer Berbasis Kabel Serat Optic Menggunakan Metode Regresi Linear - Habib Satrio Atmojo; Hero Wintolo; Astika Ayuningtyas (Institut Teknologi Dirgantara Adisutjipto, 2022)
Fiber optic cable is the fastest computer network transmission medium today. In addition to its ability to transfer data faster than other transmission media, fiber optic cable also has factors that can interfere with its performance, one of which is bending. Experiments were carried out on fiber optic cables that were given bending, then tested the data transfer speed for 60 seconds at different bending diameter variations. The results of the test with a maximum speed of 967.35 mbps at a bending diameter of 20 mm, then the speed decreases as the bending diameter is getting smaller, and the slowest speed is at a diameter of 6 mm with a speed of 4.15 mbps. The data was then tested using the validity test, normality test, linearity test and analyzed using simple regression analysis. From the results of the study it can be concluded that there is an effect of bending on the quality of data transfer by 41%.